Sistema de gestão ambiental: estudo de caso em uma agroindústria de laticínios - Dotto, Vanessa Reuter (2012)
The environmental issue has become an unknown to the industries, especially companies medium and small sized. Pressures from society, governments and the market itself, has encouraged industries to adopt an environmentally friendly approach. The aim of this paper is to propose an Environmental Management System for a dairy agroindustry sector through a case study in a cheese factory, from the diagnosis made at the company. The methodology consisted of an exploratory, descriptive, qualitative research, with case study technique. The data collect occurred through interviews not standardized, environmental audit, tool Failure Mode and Effect Analysis (FMEA) and observation of the production environment. From the data collected were raised possibilities for improvement through the adoption of environmental management techniques in organization. The data collected also were used to realize an initial environmental assessment contemplating the following items: applicable environmental laws and regulations, environmental aspects and impacts, evaluation of practices and existent procedures, including accidents and environmental fines. Thus, it was possible to establish an environmental policy, creating a subsequent environmental management program for the industry. Thus, this proposal intends to bring a safety and environmental fitting to the industry and serve as a model base management to other industries in the dairy sector.